Students’ Gender and Their Satisfaction with Service Delivery in Federal Universities in South Nigeria - Akpoiroro, Dr Roseline M.; Okon, James (Advances in Social Sciences Research Journal, 2015)
An investigation into the gender determination of students’ satisfaction with service delivery in federal Universities in south-south geopolitical zone of Nigeria was the subject of this study. To execute the study, the hypothesis was formulated and literature reviewed. Using the stratified random sampling technique 1,700 students out of a population of 70,808 formed the study’s sample. They were Years One, Two, Three, and Four regular undergraduate students of the 2008/2009 to 2011/2012 academic years in federal universities in south-south Nigeria. Data collected for this study was obtained through a face-validated, 35-item Students’ Satisfaction with Service Delivery Questionnaire (SSSDQ) with test-retest reliability estimate of .71 to .83. The instrument was administered to the 1,700 respondents, but only 1,450 copies were properly filled and used to assess students’ satisfaction with service delivery in their universities based on their gender. Data collected was analyzed using descriptive statistics and independent t-test analysis. The major findings of the study pointed to the significant difference between male and female students in their satisfaction with the delivery of educational, library, medical, transport, security, hostel, and ICT services. Based on the findings, the conclusion was drawn. It was recommended that gender sensitivity to service delivery to university students should be observed. Key words: Sex, male, female, service delivery, students’ satisfaction.